Rebonding effect on microleakage in composite restorations - F Moshref javadi; MR Maleki pour; P Mirzakoucheki (Isfahan University of Medical Sciences, 2010)
Introduction: Microleakage is one of the most important complications of direct tooth-colored restorations. One of the described methods to reduce microleakage is the use of bonding agents after finishing restorations.The purpose of this study was to evaluate microleakage associated with class V composite restorations while using rebonding on restorative margins.Materials and Methods: A total of 48 extracted caries-free human premolars were selected. Class five cavities were prepared on the buccal surfaces of all samples. Occlusal margins were placed in enamel while gingival margins were placed in dentin.Teeth were randomly divided into four groups of 12. Group 1 was considered as the control group, which was restored without rebonding. In groups 2, 3 and 4, after finishing and polishing, rebonding was performed by Prompt L-Pop, permaseal and Clearfil SE Bond on the restoration margins respectively. Specimens were thermocycled for 500 cycles, sealed with two layers of fingernail polish except for the occlusal and gingival margins, and immersed in fuschine 2% for 24 hours. Specimens were longitudinally sectioned with diamond disk and studied under stereomicroscope. The data were analyzed with Kruskal-Wallis and wilcoxon tests. (α = 0.05).Results: Kruskal-wallis test showed no statistically significant differences for microleakage on occlusal (P value = 0.075) and gingival margins (P value = 0.281) among the groups. Wilcoxon test showed significant differences between occlusal and gingival margins in Prompt L-Pop (P value = 0.023) and permaseal (P value = 0.026) groups, but between the other groups, this difference was not significant. (P < 0.05).Conclusion: The three bonding agents applied in this study do not seem useful in decreasing microleakage into enamel and dentin margins. Key words: Rebonding, Microleakage, Composite resin restorations, Dental adhesive.